الأدب المهـجري الأنجلوفوني "كتاب خالد" لأمين الريحاني و"النبي" لجبران أنموذجا - عتيق, مديحة (Sciences humaines; Vol. 32 (2013): SCIENCES HUMAINES)
الأدب الأنجلوفوني العربي هو مجموع النصوص الإبداعية التي ألّفها بالإنجليزية مبدعون من أصول عربية، تحاول هذه الورقة أن تسلّط الضوء على ظهور الأدب الإنجلوفوني العربي الذي تعود جذوره إلى أوائل القرن العشرين في الولايات المتحدة الأمريكية  مع ظهور "كتاب خالد" لأمين الريحاني و "النبي " لجبران، ستناقش هذه الورقة    Abstract : Arab Anglophone Literature is the body of writings written in English by authors of Arab origins. This paper is an attempt to shed light on the emergence of Arab Anglophone literature which dated back to the early 1920’s in USA with the appearance of Ameen Rihani’s « The Book of Khalid  » and Gibran’s «  The Prophet » ; the paper will discuss the aesthetics , thematic topics and the readership of both works.